Analysis of head and neck cancer scRNA-seq data identified PRDM6 promotes tumor progression by modulating immune gene expression - Wu, Zhenyu; Lepcha, Thurbu Tshering; Zhou, Dawei; He, Zhixian; Fiches, Guillaume N.; Park, Youngmin; He, Jinshan; Chen, Jianwen; Shanaka, K. A. S. N.; Oghumu, Steve; Zhao, Weiqiang; Ma, Anjun; et al. (Frontiers in Immunology, 2025)
Head and neck squamous cell carcinoma (HNSCC) is a biologically aggressive and heterogeneous group of cancers with limited treatment options for patients who do not respond to standard therapies. While HPV-related HNSCCs tend to show better therapeutic outcomes, we still have limited understanding of the immune mechanisms underlying these cancers. Immune-responsive genes (IRGs) have emerged as critical factors in regulating both tumor progression and immune response. Recent advances in single-cell RNA sequencing (scRNA-seq) and the development of cell-type specific regulon inference tools, such as IRIS3, have provided new insights into the tumor immune microenvironment. In this study, we leveraged the IRIS3 platform to analyze scRNA-seq data from HNSCC patient samples, identifying novel transcription factor (TF)-IRG networks that contribute to tumor proliferation and immune escape. Specifically, we identified PRDM6, a histone methyltransferase, possesses the previously unknown role in promoting tumor cell proliferation by inducing IRG expression. We further demonstrated that HPV viral oncoproteins (E6/E7) up-regulate the PRDM6 expression, which associates PRDM6 with HPV-positive HNSCC.